PENGARUH MEDIA PEMBELAJARAN DOMAT (DOMINO MATEMATIKA) DALAM MENINGKATKAN PEMAHAMAN SIMBOL MATEMATIKA SISWA KELAS 2 DI SEKOLAH DASAR - Amna, Aisyatul; Framz Hardiansyah; Ali Armadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of the application of cards in the domino game on the mathematics learning achievement of grade 2 students in mathematics learning. The study was conducted at SDN Babbalan. The research method used was a quasi-experimental study with a post-test control Group Design research design. Sampling was carried out using the Random Sampling technique. The first research sample consisted of 33 students for the experimental class that applied the domino card game learning media, and the second sample also consisted of 32 students for the control class that applied the conventional learning model. Data analysis in both study groups used the t-test. From the results of the analysis, the results showed that the significance value was 0.043 <0.05. This indicates that the use of modified domino card media affects the mathematics learning achievement of grade 2 students in understanding mathematical symbols.